Assessment of Lifestyle pattern and Expanded Disability status scale (EDSS) in women with Multiple Sclerosis - Hasna Arshia; Sheba Jeyaraj; Senthil Nathan (The Bioscan, 2025)
The autoimmune disorder “Multiple Sclerosis” (MS) is a disease that affects the central nervous system and causes demyelination. Women are more affected. Despite growing research, there is limited understanding of the impact of nutrition and lifestyle on MS progression in India. Women with MS (30) from Multiple Sclerosis Society of India (Chennai Chapter) participated in the study. The purpose of this inspection was to study the lifestyle and its effect on “Expanded Disability Status Scale” (EDSS). Data were collected on dietary intake, physical activity levels, MS symptoms, and EDSS scores, focusing on factors such as stress, sleep disturbances, and disability levels. Participants had a mean age of 34.5±9.3 years, with disease onset at 26.8±8.04 years. Most of them were sedentary and overweight (mean BMI: 27.1±5.9 kg/m²), with 46.6% showing gain in weight after MS onset. A significant portion (93.3%) was breastfed during childhood, and 90% were not offspring of consanguineous marriages. Sleep disturbances were prevalent, with 60% reporting difficulty falling asleep. Chronic stress was the most common relapse trigger (73.3%), and 66.6% were on disease-modifying drugs. The EDSS scores showed that 33.3% were moderately disabled, and 13.3% had severe disability. An important positive connection between the time-span of MS and EDSS was noticed, indicating that longer disease duration is strongly associated with greater disability. This study suggests that women with MS in India face significant challenges in terms of lifestyle, which can contribute to increased disability. Both nutritional education and lifestyle modifications can positively impact symptoms and should be integrated into MS care.